Life-course leisure-time physical activity trajectories in relation to health-related behaviors in adulthood: the Cardiovascular Risk in Young Finns study - Irinja Lounassalo; Mirja Hirvensalo; Sanna Palomäki; Kasper Salin; Asko Tolvanen; Katja Pahkala; Suvi Rovio; Mikael Fogelholm; Xiaolin Yang; Nina Hutri-Kähönen; Olli T. Raitakari; Tuija H. Tammelin (BMC, 2021)
Abstract Background Evidence on whether leisure-time physical activity (LTPA) facilitates individuals' adoption of multiple healthy behaviors remains scarce. This study investigated the associations of diverse longitudinal LTPA trajectories from childhood to adulthood with diet, screen time, smoking, binge drinking, sleep difficulties, and sleep duration in adulthood. Methods Data were drawn from the Cardiovascular Risk in Young Finns Study. Participants were aged 9-18 years (N = 3553; 51% females) in 1980 and 33-49 years at the latest follow-up in 2011. The LTPA trajectories were identified using a latent profile analysis. Differences in self-reported health-related behaviors across the LTPA trajectories were studied separately for women and men by using the Bolck-Croon-Hagenaars approach. Models were adjusted for age, body mass index, education level, marital status, total energy intake and previous corresponding behaviors. Results Persistently active, persistently low-active, decreasingly and increasingly active trajectories were identified in both genders and an additional inactive trajectory for women. After adjusting the models with the above-mentioned covariates, the inactive women had an unhealthier diet than the women in the other trajectories (p <  0.01; effect size (ES) > 0.50). The low-active men followed an unhealthier diet than the persistently and increasingly active men (p <  0.01; ES > 0.50). Compared to their inactive and low-active peers, smoking frequency was lower in the increasingly active women and men (p <  0.01; ES > 0.20) and persistently active men (p <  0.05; ES > 0.20). The increasingly active men reported lower screen time than the low-active (p <  0.001; ES > 0.50) and persistently active (p <  0.05; ES > 0.20) men. The increasingly and persistently active women reported fewer sleep difficulties than the inactive (p <  0.001; ES > 0.80) and low-active (p <  0.05; ES > 0.50 and > 0.80, respectively) women. Sleep duration and binge drinking were not associated with the LTPA trajectories in either gender, nor were sleep difficulties in men and screen time in women. Conclusions Not only persistently higher LTPA but also an increasing tendency to engage in LTPA after childhood/adolescence were associated with healthier diet and lower smoking frequency in both genders, having less sleep difficulties in women and lower screen time in increasingly active men. Inactivity and low activity were associated with the accumulation of several unhealthy behaviors in adulthood. Associations were stronger in women.